ADUAN SAPI DI BONDOWOSO ANTARA TRADISI, JUDI, DAN POLITIK - Bambang Samsu Badriyanto (Faculty of Humanities, Jember University, 2012)
Bull fighting is a form of physical fight involving two bulls guided by two jokey (seler) found in Bondowoso regency. This performance emerged in line with the birth of the Bondowoso in the 19th century, initiated by Ki Ronggo, the central figure in the opening up of Bondowoso. Initially, the bull fighting had an amusement function, but then turned into a gambling arena. A shift from an amusement to a gambling arena had been strongly influenced by the ethnical characters of Madurese associated with violence and competition. Religious image linked ti this ethnic group could not prevent them from practicing gamble in the bull fighting festival. There had been a form of dependency between bull fighting, gambling, and the government as the holder of legal authority. A bull fighting without gambling would not attract spectators and without them the government could not make money from tax. In 1991, for example, the bull fighting made a contribution of 15 % of the Bondowoso’s total income. A political shift in Bondowoso from a nationalist, Golkardominated political power to a religious, PKB dominated political power caused the ban of the bull fighting festival due to religious reasons.Keywords: bull fighting, Madurese ethnic, Bondowoso